The antecedents of customer loyalty in Tabung Haji, Malaysia from depositors perspective / Fathin Najehah Ab Rashid - Ab Rashid, Fathin Najehah (2018)
Customer loyalty has been a vital concern for each and every institution. This is because attracting new customer would cost much higher than maintaining the current ones. Therefore, every institution would pay extra attention in gaining a loyal customer. This study attempts to determine the factors that affecting customer loyalty toward Tabung Haji, Malaysia. The study was carried out by conducting a survey questionnaire to 120 random depositors of Tabung Haji. Service quality, customer satisfaction and trust are the factor that has been investigates in this study. The variables are chosen because these factors are commonly used in the previous studies. The study showed that the level of loyalty is high at a mean of 3.2476 based on four likert scale. The study also showed that customer satisfaction is the most significant factor in influencing customer loyalty in Tabung Haji. The SPSS software is used to analyse the data gathered from the respondents.